Robots [ designed to meet almost any need (Understanding Robotics, 2005)
This video series shows students how robots work...their capabilities and limitations...and how they will influence the future. Viewers watch robots perform various tasks and see close-ups of components. The video compares robots with two axes to robots with ten axes and explains the differences in the types of jobs they do. Also covered are the work envelope and the operation parameters